PENYULUHAN KESEHATAN LINGKUNGAN MELALUI SANITASI DAN KEBERSIHAN LINGKUNGAN SEBAGAI UPAYA PENINGKATAN KUALITAS KESEHATAN MASYARAKAT DI KAMPUNG SOSKOTEK DISTRIK KAURE KABUPATEN JAYPURA - Maklon Warpur; Yunus P. Paulangan (LPPM Uncen, 2021)
The counseling activities of environmental health through environmental sanitation and hygiene as an effort to improve the quality of public health in Soslotek Village, Kaure District Jayapura Regency, have been conducted on August 20, 2020. The activity aims to motivate the community about the importance of maintaining cleanliness and environmental health in supporting community health, as well as to provide understanding to the community in protecting the environment in order to avoid diseases caused by an unhealthy environment. The methods used in this activity were lectures, discussions and questions as well as answers. This activity has succeeded in involving 26 people from various backgrounds such as youth, students, mothers and fathers. The implementation of counseling activity of environmental health began with self-introduction by the team of presenters, then the team of presenters tried to dig basic knowledge of the community about sanitation and environmental hygiene through the introduction of the surrounding environment such as the use of environmental units for settlements, gardening, traditional ceremonies, bathing, and washing as well as latrines (MCK). After obtaining information about the basic knowledge of the community, the team of community service activity then presented the important materials of environmental health about how to manage a good environment to create a clean and healthy environment. With the existence of this community service activity on environmental health, hopefully it can increase the knowledge of the residents of Soskotek Village about a style of healthy life for the sake of creating a better quality of life, and is able to increase the awareness of the people of Soskotek Village to participate actively in maintaining cleanliness and environmental health.Keywords: : environmental, management, sanitation, community, jayapura